Training on Innovation in Public Administration Management: Building Information Systems for Transparency and Accountability - Abiyasa Eka Saputra; Devi Rahmah Sope; Marnoto Marnoto; Sopi Sopi; Said Hamzali (PT. Global Research Collaboration, 2024)
Kemang Sub-district, Bogor Regency, aims to improve transparency, accountability, and efficiency in public services through the application of information technology. The main challenges faced by this village are limited utilization of technology, lack of transparency, and limited accountability in the management of village funds. To address these issues, a training was conducted that included needs identification, module development, face-to-face and online training, hands-on practice, and mentoring and evaluation. The results of the training showed an increase in the skills of village officials in using information systems, increased community participation in decision-making, and improved administrative efficiency. The developed village information system allows the community to access information related to village activities and budgets in a transparent manner, thus increasing community trust in the village government. Collaboration with NGOs and educational institutions also provided the necessary support in developing the village information system. Thus, this training not only increases the capacity of village officials, but also supports participatory and sustainable development in Pondok Udik Village.